The effects of kisspeptin on β-cell function, serum metabolites and appetite in humans - Izzi-Engbeaya,CN; Comninos,AN; Clarke,S; Abbara,A; Lewis,M; Holmes,E; Nicholson,J; Tan,T; Rutter,G; Dhillo,W (Diabetes, Obesity and Metabolism, 2018)
AimsTo investigate the effect of kisspeptin on glucosestimulated insulin secretion and appetite in humans.Materials and methodsIn 15 healthy men (age: 25.2 ± 1.1 years; BMI: 22.3 ± 0.5 kg m−2), we compared the effects of 1 nmol kg−1 h−1 kisspeptin versus vehicle administration on glucosestimulated insulin secretion, metabolites, gut hormones, appetite and food intake. In addition, we assessed the effect of kisspeptin on glucosestimulated insulin secretion in vitro in human pancreatic islets and a human βcell line (EndoCβH1 cells).ResultsKisspeptin administration to healthy men enhanced insulin secretion following an intravenous glucose load, and modulated serum metabolites. In keeping with this, kisspeptin increased glucosestimulated insulin secretion from human islets and a human pancreatic cell line in vitro. In addition, kisspeptin administration did not alter gut hormones, appetite or food intake in healthy men.ConclusionsCollectively, these data demonstrate for the first time a beneficial role for kisspeptin in insulin secretion in humans in vivo. This has important implications for our understanding of the links between reproduction and metabolism in humans, as well as for the ongoing translational development of kisspeptinbased therapies for reproductive and potentially metabolic conditions.